Deskripsi Kemampuan Pemecahan Masalah dengan Menggunakan Model Pembelajaran Problem Based Learning (PBL) Peserta Didik Kelas VIII SMPN 18 Makassar - Aswir Aswir; Hasanuddin Hasanuddin; Ramlawati Ramlawati (Universitas Negeri Makassar, 2025)
This research is a quantitative descriptive survey research that aims to describe the problem-solving abilities of class VIII students of SMPN 18 Makassar for the 2022/2023 academic year in the material of vibrations, waves, and sound. The population in this study were all class VIII students at SMP Negeri 18 Makassar in the 2022/2023 academic year consisting of 10 classes with a total of 267 students. The sampling technique used by researchers is a purposive sampling technique in which the sampling technique is carried out according to the wishes of the researcher with the consideration that is looking at the average value of learning outcomes. In this study, the sample used was 1 class, namely class VIII 8 with a total of 24 students. The research instrument was in the form of problem solving ability test questions. Data collection was carried out by giving students a problem-solving ability test which was made in the form of an essay of 10 questions. The results of the study show the problem solving abilities of class VIII students at SMPN 18 Makassar; (1) on the indicator of understanding the problem in the